(untitled) (Journal of Environmental Science and Natural Resources, 2017)
An experiment was conducted in the experimental farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur to evaluate the efficacy of IPM packages for suppressing aphid and pod borer of summer country bean BARI Seem-3. In case of aphid, among the different IPM packages, P4 [comprising mechanical control (hand picking) and 4 sprays of admire 50 SP (imidacloprid) @ 1ml l-1 of water at 7 days interval] had minimum inflorescence infestation (4.99), whereas untreated control plot P7 totally overturned. In case of pod borer, among the IPM packages, P5 [comprising mechanical control, hand picking with 4 sprays of ripcord 10 EC (cypermethrin) @ 1 ml l-1 of water at 7 days interval] ensured minimum inflorescence and pod infestation (by number and weight) and pod diameter with the lowest pest incidence (4.59 %). In consideration of the economic analysis of the different management packages for controlling pod borer of country bean, the highest BCR ratio (4.28) was recorded in the P5 [comprising mechanical control, hand picking with 4 sprays of ripcord 10 EC (cypermethrin) @ 1 ml l-1 of water at 7 days interval] followed by 3.76 in P6. However, based on marketable pod yield and BCR, hand picking with 4 sprays of ripcord 10 EC (cypermethrin) @ 1 ml l-1 of water at 7 days interval may be considered as the most effective option. J. Environ. Sci. & Natural Resources, 10(1): 109-115 2017